Optimalisasi Pembelajaran Bahasa Arab Generasi Z: Efek Gamifikasi Quizizz pada Hasil Belajar Siswa Madrasah - Ni’mah, Sani Maulidatun; Baihaqi, M. (Tarbiyatuna: Jurnal Pendidikan Ilmiah, 2025)
The transformation of the digital era demands innovative learning strategies that align with the characteristics of Generation Z. One promising approach is gamification, which integrates game elements into the learning process, with Quizizz being one of the most popular platforms. This study aims to examine the effectiveness of Quizizz in improving Arabic learning outcomes among tenth-grade students at MAN 1 Gresik. The research employed a quasi-experimental method with a Nonequivalent Control Group Design, involving 37 students from class X-10 as the experimental group and 38 students from class X-12 as the control group. The research instrument was a learning achievement test (pre-test and post-test), and the data were analyzed using normality, homogeneity, and independent samples t-test. The results showed that the mean post-test score of the experimental group was 86.38, while the control group obtained 79.21, with a mean difference of 7.17 points. The independent samples t-test revealed a count of 9.187 with a significance value (Sig. 2-tailed) < 0.001, indicating a statistically significant difference between the two groups. The normality test (p > 0.05) and homogeneity test (Sig. = 0.823) confirmed that the data met the assumptions for parametric analysis. Therefore, it can be concluded that Quizizz-based gamification is effective in improving Arabic learning outcomes, creating an interactive, engaging, and enjoyable learning environment that aligns with the characteristics of digital-native learners.